Life Experience of Pregnant Woman with Gestational Diabetes Mellitus in Maternal Role Attainment in Special Region of Yogyakarta - Indah Wulaningsih; Elsi Dwi Hapsari; Heny Suseani Pangastuti; Robert Priharjo (Universitas Airlangga, 2020)
Introduction: Gestational Diabetes Mellitus (GDM) is any abnormal carbohydrate intolerance that begins or is ﬁrst recognized during pregnancy. The presence of GDM has important implications for both the baby and the mother. Objective: This study explored life experience of pregnant woman with GDM in maternal role attainment. Methods: This was a phenomenological approach qualitative research. Participants were 12 mothers who gave birth to a maximum of 1 year with a history of GDM selected by purposive sampling technique with sampling criteria. Data analysis used the Colaizzi method (2011). Results: There were eight categories, e.g. the experience of the mother in GDM diagnosis; the influence GDM of the pregnancy; mother's experience in trying hard to keep her pregnancy; a variation of life experience of mothers during pregnancy, childbirth, and post-delivery; the perception of mother of her role being a mother, the factors that support the development and achievement of the maternal role attainment; the mother's experience in integrating the identity of her role as mother; gap and the desire of the mother with GDM in receiving health services. Life experience of GDM mothers in achieving maternal role attainment has a diversity. Discussion: Pregnant mothers with GDM experience various maternal role attainments. They cannot attain the role optimally.